Juridical Analysis Of The Status Of Orient Riwu Kore In The Election Of The Regional Head Of Sabu Raijua Regency In 2020 - Bill Nope; Gerald Aldytia Bunga (Journal of Digital Law and Policy, 2022)
In the 2020 Sabu Raijua regional head election, one of the regional head candidates, namely Orient P Riwukore, was questioned the status of his candidacy in the regional head election because he was suspected of being a citizen of the United States but at the same time he also had legitimate Indonesian citizenship documents. Therefore, this study aims to examine how citizenship is regulated in Indonesian and United States law and whether the Constitutional Court's decision in case number 135/PHP.BUP-XIX/2021 is constitutional. The results showed that Orient Riwu Kore was a citizen of the United States and had lost his Indonesian citizenship. Therefore, the decision of the constitutional court which annulled the victory of Orient Riwukore and his partner and ordered a re-election in Sabu Raijua Regency was a constitutional decision.